A day with the Faculty of Business and Management (FBM) - UiTM, Faculty of Business and Management (UiTM, 2023)
A one-day program with the Faculty of Business and Management was organized by the administration division of the faculty on October 11, 2023. The purpose of this program is to facilitate the dissemination of guidance and information pertaining to the academic faculty and administration. The program commenced with an Academic Meeting of the faculty and all academics, during which the Dean of the Faculty, YBhg. Professor Dr. Firdaus Abdullah reviewed academic concerns such as lecture hours and concerns about infrastructural facilities. Next, Associate Professor Dr. Md. Noor Mamat (ACIS lecturer) gave a knowledge-sharing session titled "Happy Working".